Pengaruh Penggunaan Crumb Rubber sebagai Substitusi Agregat Halus terhadap Kuat Tekan Beton Tidak Bertulang - Suganda, Defri; Fahri, Tengku Muhammad; Nasution, Adinda Juwita; Ridha, Muhammad Abdhi; Hutasuhut, Syafrida Hanum (Program Studi Teknik Mesin, Universitas HKBP Nommensen, Medan, 2025)
This study aims to analyze the effect of using crumb rubber (used tire powder) as a partial substitution of fine aggregate in unreinforced concrete. especially compressive strength and concrete weight. Crumb rubber variations used were 0%, 5%, 15%, and 25% of the volume of fine aggregate. Tests were conducted on 15 cm × 30 cm cylindrical specimens treated for 28 days. The main parameters tested included compressive strength and water absorption. The results showed that the addition of crumb rubber decreased the compressive strength of concrete significantly, the highest compressive strength was obtained in normal concrete (25.8 MPa), while the mixture of 25% crumb rubber produced the lowest compressive strength (3.9 MPa). However, it provides advantages in terms of lighter specific gravity and better water absorption. However, the addition of crumb rubber reduced the weight of the concrete by 19.4%. The use of crumb rubber at 5% is considered the most optimal alternative with a decrease in compressive strength that is still within the tolerance limit for non-structural concrete. This research supports the utilization of waste tires as an effort to support sustainable development. Keywords: crumb rubber, non-reinforced concrete, waste tires, compressive strength, lightweight concrete